2010
DOI: 10.2174/156652410791065327
|View full text |Cite
|
Sign up to set email alerts
|

The Role of PEDF in Tumor Growth and Metastasis

Abstract: Pigment epithelium-derived factor (PEDF), one of the non-inhibitory serpines, is widely expressed throughout the body. Although PEDF was initially identified as a neuronal differentiation factor, more attention has been paid to its anti-angiogenic activity. Additionally, recent researches have demonstrated that PEDF has an anti-tumor effect against several human neoplasms. This review focuses on the pathological role of PEDF in tumors, especially tumor growth and metastasis. PEDF is an endogenous anti-tumor fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…PEDF and VEGF have an inverse relationship with each other, especially in cancer in which low levels of PEDF are associated with the increased incidence of metastasis and poor malignancy prognosis (43). PEDF suppressed proliferation and induced apoptosis of the tumor cell (44). The increased ratio of VEGF/PEDF is required for angiogenesis and tumor growth.…”
Section: Discussionmentioning
confidence: 97%
“…PEDF and VEGF have an inverse relationship with each other, especially in cancer in which low levels of PEDF are associated with the increased incidence of metastasis and poor malignancy prognosis (43). PEDF suppressed proliferation and induced apoptosis of the tumor cell (44). The increased ratio of VEGF/PEDF is required for angiogenesis and tumor growth.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies have demonstrated that PEDF is an effective inhibitor of angiogenesis and has promising efficacy in the treatment of some tumors (16)(17)(18). In women with endometriosis, increased angiogenic activity has been demonstrated in peritoneal fluid, and strong expression of angiogenic factor has been demonstrated in active lesions (3,4).…”
mentioning
confidence: 99%
“…It is believed that PEDF has neuroprotectiveproperties (10) acts as an antioxidant and antiinflammatory agent (11) inhibits cellular proliferation and supports cell differentiation. (12) …”
Section: Resultsmentioning
confidence: 99%